Politeness Strategies and Gendered Language Use in Hospitality Discourse: A Case Study from an Urban Hotel in Jakarta - Wulan Dari, Desti; Aprilia, Fitria; Neisya, Neisya (ENGLISH FRANCA : Academic Journal of English Language and Education, 2025)
This research examines the utilization of politeness strategies and gendered language among hospitality professionals at Ibis Styles Jakarta Mangga Dua Square. The main goals are threefold: to find out what kinds of politeness strategies front office staff use, to look at how gender affects the language choices they make when talking to guests, and to look at how important these strategies are for improving customer satisfaction and professional communication. Data were gathered via direct observation of daily service interactions and semi-structured interviews with staff, facilitating a comprehensive understanding of both practice and perception. The analysis shows that people often use both positive and negative politeness strategies. However, the way they use them depends on their gender. Female staff members were more likely to use both positive strategies, like friendly greetings and building solidarity, and negative strategies, like indirect requests and polite apologies. This shows that they were relational and empathetic. In contrast, male staff members mostly used positive politeness strategies that focused on being clear, confident, and efficient, especially when they were busy serving customers. These gendered differences exemplify overarching discourse patterns, including "rapport talk" and "report talk," thereby affirming that communication styles are influenced by both personal preferences and societal expectations, as well as professional standards. The findings underscore that linguistic strategies are not solely a matter of decorum but serve as essential instruments in fostering guest satisfaction and professional credibility. The study contends that neither empathetic nor efficiency-driven approaches should be favored; instead, both fulfill complementary roles in hospitality service delivery. By placing these insights in the context of actual hospitality practices, the research enhances applied linguistics, discourse studies, and hospitality management. It also has real-world effects on professional training and staff development programs that want to improve communication, flexibility, and service excellence in the global hospitality industry.